Phylogenetic clustering of fungal communities in human‐disturbed streams. Issue 3 (31st March 2016) - Mykrä, H.; Tolkkinen, M.; Markkola, A. M.; Pirttilä, A.‐M.; Muotka, T.
Abstract: Phylogenetic community structure is increasingly used to examine community assembly, but the influence of anthropogenic disturbance on phylogenetic community structure remains little explored. We examined how land‐use disturbance (forestry and agriculture) and naturally harsh environmental conditions (geologically driven acidity) affect the phylogenetic diversity of stream fungi. Using DNA from decomposing alder leaves, we calculated phylogenetic distances among fungal operational taxonomic units (OTUs). Closely related OTUs co‐occurred more often than expected by chance, but partitioning the relationship between phylogeny and niche differences showed evidence for niche conservatism only at short phylogenetic distances. Communities in human‐disturbed streams were phylogenetically clustered, whereas they were over‐dispersed in circumneutral near‐pristine streams. OTU richness did not decrease with disturbance; instead, some fungal taxa were replaced by closely related, more tolerant taxa. Fungal communities in naturally acidic reference streams also showed a tendency toward phylogenetic clustering, although much less so than in disturbed streams. Our results indicate different coexistence mechanisms in different environmental settings and a strong role for anthropogenic disturbance as a selective filter shaping the phylogenetic structure of instream fungal communities. The effects of human disturbances on the phylogenetic community structure of fungi occurred independently of taxonomic structure, suggesting utility of phylogenetic approaches to bioassessment.